An overview of ibra' implementation in Malaysian Islamic Banks / Mohd Ab Malek Md Shah … [et al.] - Md Shah, Mohd Ab Malek; Mohd Jody, Jeniwaty; Shahudin, Mohd Harun; Mahzan, Sulaiman (Academy of Contemporary Islamic Studies, 2016)
In the normal conventional banking system, customer only has to pay the outstanding principal amount and earned interest at the time when early settlement is made. The financier normally waives the unearned interest. Contractually, customer in Islamic banks has to settle all outstanding selling prices in the case of early settlement. Nevertheless, Islamic bank normally gives ibra' to its customer who made early settlement. This practice of rebate is important to maintain the competitiveness of Islamic banking as a mechanism of providing mutual help in terms of charitable matters within a Muslim society, which is highly recommended by shariah principles. This concept is actually more suitable for the financier who wants to surrender its right over the debt to customers. Hence, this paper aimed to explore the fundamental concept of ibra' as practised by the bankers currently within the ambit of Islamic teaching. In addition, it is hoped that; throughout this study, it would lead to the betterment of understanding of this concept holistically.